LOGIKA FUZZY DALAM SISTEM PENGAMBILAN KEPUTUSAN PENERIMAAN BEASISWA - Siti Komariyah; Riza M. Yunus; Sandi Fajar Rodiyansyah (PROCEEDING STIMA)
The decision making process in determining the right to receive the scholarship are often subjective, where there are some university students who have the ability or value that is not so different. so needed it is presence the systems that support decision making that can be used to simplify the determination of who is entitled to receive a scholarship. This system is supported by Tsukamoto fuzzy logic method that is based on the data and rules of human resources with the criteria set by the group of people. The result of this process is given to university students who are in decision-making on the basis of the acceptance of the scholarship. This software is made by using a MySQL database and IDE netbeans programme language as an instrument by which this application can help in the decision making process scholarship acceptance quickly and accurately.Keywords: Decision Making System, Scholarship, and Tsukamoto Fuzzy Logic.